Pulled elbow can easily be diagnosed and reduced by pediatricians - A clinic-based study on 49 cases - Biswas, Biswajit; Das, Mousumi; Roy, Atanu; Konar, Mithun; Mondal, Monojit; Sil, Archan (Asian Journal of Medical Sciences, 2020)
Background: Pulled elbow is a common injury of early childhood that results in subluxation of the annular ligament due to a sudden longitudinal traction applied to the hand. Treatment is usually closed reduction with either a supination-flexion or a hyperpronation technique. Aims and Objectives: Present study is aimed to make pediatricians aware of the fact that most of such cases can be easily diagnosed and successfully reduced in office settings without much fear and complications. Materials and Methods: All cases with typical history and clinical presentation were included in the study and were subjected to supination-flexion maneuver. When the first attempt failed, a second attempt using the same technique was performed. After failure of the second attempt, hyperpronation was tried. Results: Among 49 patients included in the study, 27 (55.10 %) were girls and 22 (44.89 %) were boys. Mean age at presentation was 20.12 months. All of them were below 4 years of age. Forty-five patients were successfully reduced on the first attempt using supination-flexion maneuver, 2 patients required a second attempt using same technique. One patient was reduced with hyperpronation technique 15 minutes after first 2 attempts failed. Only 1 patient required referral to an orthopedic expert as all 3 attempts were in vain, but the child eventually recovered. Conclusion: All pediatricians should learn to diagnose and treat the condition to reduce delay in treatment and avoid complications.